Differential Bottom‐Up Control of Planktonic and Sedimentary Bacterial Communities by Phytoplankton and Extracellular Enzymes in an Asymmetric River Confluence - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Bing Yu; Xian Xu; Zhaotong Chen; Yushan Li; Zhiwei Zhu (Molecular Ecology, 2026)
Bacterial community dynamics underlie ecosystem functioning in river networks, yet how different bacterial lifestyles respond to bottom‐up biotic drivers under confluence‐induced hydraulics remains unclear. Here, we quantified spatial heterogeneity in free‐living (FL), particle‐associated (PA) and sedimentary (S) bacterial assemblages, coupled with phytoplankton and extracellular enzyme profiles, at the Yellow River‐Fenhe River confluence during the summer wet season. Clear habitat partitioning emerged, with stronger divergence at the water–sediment interface than between the two planktonic fractions (FL vs. PA). Hydrological source tracking showed that Fenhe River‐derived taxa dominated both water and sediment within the confluence reaches, whereas Yellow River lineages prevailed in the downstream reaches. Community assembly shifted hierarchically: homogeneous selection dominated FL assemblages but declined progressively toward PA and sedimentary fractions, while dispersal limitation intensified in tandem with niche contraction. Multivariate analyses showed that in addition to physicochemical factors, enzyme activity is the strongest factor predicting FL communities, explaining 43.6% of variability, whereas the phytoplankton community best predicted PA communities (68.8%). Sedimentary communities correlated weakly with phytoplankton associations (21.8%) and showed no significant link with enzyme activity. Our findings identify phytoplankton communities and enzymatic potential as key bottom‐up drivers whose relative importance varies with bacterial lifestyle, providing mechanistic insight into biophysical dynamics within river‐confluence ecosystems.